Formas de ureia e doses de nitrogênio em cobertura na qualidade fisiológica de sementes de trigo - Prando, André Mateus (2012)
Besides increasing productivity, nitrogen fertilization may have positives effects on seed physiological quality. The objective of this study was to evaluate the effect of different forms and levels of urea in top dressing fertilization on the physiological quality of wheat seed genotypes. Seeds of three wheat genotypes (BRS 208, BRS Pardela and IWT 04008) were evaluated for four levels of nitrogen fertilization (0, 40, 80 and 120 kg.ha-1) in three forms of urea (conventional urea, urea with urease inhibitor and protected urea). The nitrogen fertilization was applied during tillering, 20 days after emergence. The seed nitrogen content, 1000 seed mass, germination and vigor (germination first count, cold test, seedling emergence in the field, dry weight of seedlings, accelerated aging and electrical conductivity) were evaluated. The IWT 04008 line and the cultivar BRS Pardela had seeds with a higher physiological quality than those of the cultivar BRS 208. The forms of urea and levels of nitrogen in topdressing did not affect seed physiological quality of the different wheat genotypes.